On the destruction limit of Si power diodes during reverse recovery with dynamic avalanche. - Domeij, M. (IEEE Transactions on electron devices)
The reverse recovery destruction limit of 3.3 kV fast recovery diodes was investigated by measurements and device simulations. Based on a good agreement between the measured destruction limit and current filamentation in simulations, it is proposed that the destruction is triggered by the onset of impact ionization at the n-n+ junction. The proposed destruction mode has significant similarities with previously described second breakdown at the static breakdown voltage. An approximate analytical model which was derived indicates that avalanche at the n-n+ junction should become unstable with a time constant on the order of nanoseconds, whereas dynamic avalanche at the p-n junction should be stable. Simulations and measurements show that the reverse recovery safe operating area depends on the n-base width. An approximate equation is proposed to determine the minimum n-base width required for a nondestructive reverse recovery with dynamic avalanche as a function of the reverse peak voltage.